From PSM to Helping Behavior in the Contemporary Greek Public Sector: The Roles of Organizational Identification and Job Satisfaction. Issue 6 (2nd November 2019) - Karolidis, Dimitrios; Vouzas, Fotis
Abstract: This article investigates helping behavior (HB), a fundamental dimension of organizational citizenship behavior (OCB), in the context of the contemporary Greek public sector. More specifically, the effect of public service motivation on helping behavior is examined through the indirect effects of organizational identification and job satisfaction. Reported data were gathered from 322 respondents with the aid of a questionnaire administered to central and regional Greek public service units. The findings indicate that there is a strong relationship between helping behavior and public service motivation, while organizational identification and job satisfaction act as mediators and moderators of this relationship, respectively. This research extends the current organizational literature by illustrating the mediating role of organizational identification and the moderating role of job satisfaction in the effect of public service motivation on helping behavior. By studying the behaviors and motives of public servants, this research contributes to our knowledge of what drives these individuals and the methods for managing these employees. These findings can be used as an input in the development of specific human resource management strategies aimed at improving organizational success in contemporary public-sector settings.